Imposing accurate wall boundary conditions in corrective‐matrix‐based moving particle semi‐implicit method for free surface flow. (6th August 2020) - Duan, Guangtao; Matsunaga, Takuya; Yamaji, Akifumi; Koshizuka, Seiichi; Sakai, Mikio
Summary: Corrective matrix that is derived to restore consistency of discretization schemes can significantly enhance accuracy for the inside particles in the Moving Particle Semi‐implicit method. In this situation, the error due to free surface and wall boundaries becomes dominant. Based on the recent study on Neumann boundary condition (Matsunaga et al, CMAME, 2020), the corrective matrix schemes in MPS are generalized to straightforwardly and accurately impose Neumann boundary condition. However, the new schemes can still easily trigger instability at free surface because of the biased error caused by the incomplete/biased neighbor support. Therefore, the existing stable schemes based on virtual particles and conservative gradient models are applied to free surface and nearby particles to produce a stable transitional layer at free surface. The new corrective matrix schemes are only applied to the particles under the stable transitional layer for improving the wall boundary conditions. Three numerical examples of free surface flows demonstrate that the proposed method can help to reduce the pressure/velocity fluctuations and hence enhance accuracy further. Abstract : The MPS corrective matrix schemes are newly generalized to incorporate the straightforward and accurate treatment of Neumann boundary condition. The numerical examples of free surface flows demonstrated the proposed method could further improve the accuracy and the stability such as spurious fluctuations of pressure and velocity in comparison to those of the existing one.